Evaluation of Flood Disaster with Canopy Density Analysis in Batu: Mitigation Strategy through Coffee Agroforestry - Burhanuddin, Achmad Dadang; Nisa, Nur Islakhun (Directorate of Research and Community Services, 2025)
Flash floods that struck Bumi Aji, Batu City, in 2021 were a direct consequence of environmental degradation, primarily the loss of water catchment areas due to land-use change and must restoration strategy. This study aims to: (1) analyze the decline in canopy density using Geographic Information System (GIS) and the Normalized Difference Vegetation Index (NDVI), (2) assess the impact of this decline on flood vulnerability, and (3) formulate a strategic mitigation model with coffee agroforestry. Through a time-series analysis of satellite imagery (<2000 to 2020), the research identifies significant land degradation, particularly on the northern slopes of Mount Arjuno, where vegetation cover decreased by approximately 40% due to agricultural expansion. This reduction diminishes water infiltration and increases surface runoff, heightening flood risk. In response, this paper proposes a strategic shift to coffee-based agroforestry as a sustainable land conservation model. This approach directly restores a multi-layered canopy, which improves soil structure and reduces erosion. Furthermore, it offers economic resilience for local communities through diversified income. Implementing coffee agroforestry is presented as a synergistic strategy that aligns with Bumi Aji's agrotourism potential while effectively mitigating future flood disasters through ecological restoration.